Detoxification Cytochrome P450s (CYPs) in Families 1–3 Produce Functional Oxylipins from Polyunsaturated Fatty Acids - Jazmine A. Eccles; William S. Baldwin (Cells, 2022)
This manuscript reviews the CYP-mediated production of oxylipins and the current known function of these diverse set of oxylipins with emphasis on the detoxification CYPs in families 1–3. Our knowledge of oxylipin function has greatly increased over the past 3–7 years with new theories on stability and function. This includes a significant amount of new information on oxylipins produced from linoleic acid (LA) and the omega-3 PUFA-derived oxylipins such as α-linolenic acid (ALA), docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA). However, there is still a lack of knowledge regarding the primary CYP responsible for producing specific oxylipins, and a lack of mechanistic insight for some clinical associations between outcomes and oxylipin levels. In addition, the role of CYPs in the production of oxylipins as signaling molecules for obesity, energy utilization, and development have increased greatly with potential interactions between diet, endocrinology, and pharmacology/toxicology due to nuclear receptor mediated CYP induction, CYP inhibition, and receptor interactions/crosstalk. The potential for diet-diet and diet-drug/chemical interactions is high given that these promiscuous CYPs metabolize a plethora of different endogenous and exogenous chemicals.